2021
DOI: 10.1002/ijc.33859
|View full text |Cite
|
Sign up to set email alerts
|

NKG2A is a late immune checkpoint on CD8 T cells and marks repeated stimulation and cell division

Abstract: The surface inhibitory receptor NKG2A forms heterodimers with the invariant CD94 chain and is expressed on a subset of activated CD8 T cells. As antibodies to block NKG2A are currently tested in several efficacy trials for different tumor indications, it is important to characterize the NKG2A+ CD8 T cell population in the context of other inhibitory receptors. Here we used a well‐controlled culture system to study the kinetics of inhibitory receptor expression. Naïve mouse CD8 T cells were synchronously and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
3
20
1
Order By: Relevance
“…Dual anti-NKG2A/-PD-L1 immunotherapy, added as an adjuvant to ATRi/RT, drives significant infiltration of PD-1 high /proliferative/effector memory cytotoxic CD8 and CD4 conv T cells in tumours. We found that addition of anti-NKG2A antibody to the combination was essential to shifting the cell cycle towards the G2/M phase in T cells, which was in line with previous data showing repeated cell division in NKG2A + CD8 T cells 33 . These results are also consistent with findings of elevated proliferative capacity of CD8 T cells in response to combined RT and dual NKG2A/PD-1 blockade 34 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Dual anti-NKG2A/-PD-L1 immunotherapy, added as an adjuvant to ATRi/RT, drives significant infiltration of PD-1 high /proliferative/effector memory cytotoxic CD8 and CD4 conv T cells in tumours. We found that addition of anti-NKG2A antibody to the combination was essential to shifting the cell cycle towards the G2/M phase in T cells, which was in line with previous data showing repeated cell division in NKG2A + CD8 T cells 33 . These results are also consistent with findings of elevated proliferative capacity of CD8 T cells in response to combined RT and dual NKG2A/PD-1 blockade 34 .…”
Section: Discussionsupporting
confidence: 92%
“…Enhanced antitumour functions of NKG2A + CD8 T cells have been described in previous studies. NKG2A was reported to be a late immune checkpoint and NKG2A expression in CD8 T cells was associated with repeated stimulation and cell division 32, 33 . NKG2A-positive clusters of CD8 T cells in head and neck cancer patients were enriched for other immune checkpoints, including PD-1, TIM-3 and CD39 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In γδT cells, NKG2A receptor-mediated inhibitory signaling tends to prevail [ 109 ]. NKG2A+ and NKG2A- cells can be formed from γδT cells during early thymic development and do not appear to change significantly with cell growth [ 110 ], and their expression kinetics are similar to those of cells expressing TIM-3 and CD39, which emerge late but are stably expressed [ 111 ]. The combination of HLA-E with NKG2A, dependent on the participation of ITIMs and SHP1/2, can transmit inhibitory signals to interfere with the activation of γδT cells and limit the function of effector γδT cells.…”
Section: Interaction Between the Tme And γδT Cellsmentioning
confidence: 99%
“…In addition to a role in NK cell immunity, CD94-NKG2A is also expressed by activated/exhausted T cells in response to chronic antigen stimulation [13] or tumour infiltration [14]. Here, CD94-NKG2A limits sustained CD8 + T-cell effector function [3] and can be upregulated under suppressive cytokines such as TGF-b [15,16]. Similarly, HLA-E/Qa-1 b overexpression by tumour cells has been attributed to enhanced tumourigenicity through appropriation of such mechanisms [17].…”
Section: Introductionmentioning
confidence: 99%